2012
DOI: 10.1155/2012/506382
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Interface Improves Oxygenation in Patients Undergoing Bronchoscopy

Abstract: During bronchoscopy hypoxemia is commonly found and oxygen supply can be delivered by interfaces fed with high gas flows. Recently, the high-flow nasal cannula (HFNC) has been introduced for oxygen therapy in adults, but they have not been used so far during bronchoscopy in adults. Forty-five patients were randomly assigned to 3 groups receiving oxygen: 40 L/min through a Venturi mask (V40, N = 15), nasal cannula (N40, N = 15), and 60 L/min through a nasal cannula (N60, N = 15) during bronchoscopy. Gas exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
109
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 22 publications
4
109
2
2
Order By: Relevance
“…Sztrymf et al 16,17 found that HFNC significantly reduced breathing frequency, heart rate, dyspnea score, supraclavicular retraction, and thoraco-abdominal synchrony and increased pulse oximetry in 38 ICU patients with acute respiratory failure; this improvement was observed as early as 15 min after the beginning of HFNC. This result was consistent with 19 during invasive procedures such as bronchoscopy, 20 and do-not-intubate patients. 21 As in this study the subjects showed relatively low levels of dyspnea (dyspnea score of Ͻ 3 points), low breathing frequency (Ͻ 25 breaths/min), and low heart rate (Ͻ 100 beats/min), one could argue that similar results may have been achieved with only the conventional oxygen therapy.…”
Section: Discussionsupporting
confidence: 84%
“…Sztrymf et al 16,17 found that HFNC significantly reduced breathing frequency, heart rate, dyspnea score, supraclavicular retraction, and thoraco-abdominal synchrony and increased pulse oximetry in 38 ICU patients with acute respiratory failure; this improvement was observed as early as 15 min after the beginning of HFNC. This result was consistent with 19 during invasive procedures such as bronchoscopy, 20 and do-not-intubate patients. 21 As in this study the subjects showed relatively low levels of dyspnea (dyspnea score of Ͻ 3 points), low breathing frequency (Ͻ 25 breaths/min), and low heart rate (Ͻ 100 beats/min), one could argue that similar results may have been achieved with only the conventional oxygen therapy.…”
Section: Discussionsupporting
confidence: 84%
“…The advantage of HFNC in terms of improving dyspnea, subject comfort, and oxygenation has also been noted in other subject populations, such as post-cardiac surgery 8 and postendotracheal extubation subjects, 7,9 and during fiberoptic bronchoscopy. 24 Several studies demonstrated that HFNC reduced breathing frequency and also improved oxygenation in subjects Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…) protect patients from hypoxaemia during bronchoscopy with remarkable tolerance and minimal variations in SpO 2 [77][78][79][80]. NIV and CPAP are usually used in more severe hypoxaemic patients during bronchoscopy and studies have shown that NIV is superior both to SOT [81][82][83] and to NHF [84].…”
Section: No Benefitmentioning
confidence: 99%
“…NIV and CPAP are usually used in more severe hypoxaemic patients during bronchoscopy and studies have shown that NIV is superior both to SOT [81][82][83] and to NHF [84]. Moreover, it seems that NHF benefits are more remarkable when bronchoscopy is performed through the nares than through the mouth; nonetheless, even if bronchoscopy is performed through the mouth, maximum flow rate (60 L·min ) should be used, since a PEEP value of 3.6 cmH 2 O has been measured at this flow rate in healthy volunteers with a partially obstructed mouth [77].…”
Section: No Benefitmentioning
confidence: 99%